2021
DOI: 10.1038/s41467-021-21130-6
|View full text |Cite
|
Sign up to set email alerts
|

Live-cell single particle tracking of PRC1 reveals a highly dynamic system with low target site occupancy

Abstract: Polycomb repressive complex 1 (PRC1) is an essential chromatin-based repressor of gene transcription. How PRC1 engages with chromatin to identify its target genes and achieve gene repression remains poorly defined, representing a major hurdle to our understanding of Polycomb system function. Here, we use genome engineering and single particle tracking to dissect how PRC1 binds to chromatin in live mouse embryonic stem cells. We observe that PRC1 is highly dynamic, with only a small fraction stably interacting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 130 publications
(203 reference statements)
6
41
0
Order By: Relevance
“…This is particularly relevant for histone modifications that are of low abundance yet highly enriched at gene regulatory elements. However, we estimate that ∼5.9 × 10 6 H2AK119ub1 molecules decorate the genome of ES cells (Huseyin and Klose 2021), and this number increases ∼1.5-fold to twofold after conditional removal of BAP1 (Fig. 1), which is comparable with the at least twofold increase in H2AK119ub1 levels reported previously in constitutive BAP1 knockout cells (Campagne et al 2019;Kolovos et al 2020).…”
Section: Discussionsupporting
confidence: 86%
“…This is particularly relevant for histone modifications that are of low abundance yet highly enriched at gene regulatory elements. However, we estimate that ∼5.9 × 10 6 H2AK119ub1 molecules decorate the genome of ES cells (Huseyin and Klose 2021), and this number increases ∼1.5-fold to twofold after conditional removal of BAP1 (Fig. 1), which is comparable with the at least twofold increase in H2AK119ub1 levels reported previously in constitutive BAP1 knockout cells (Campagne et al 2019;Kolovos et al 2020).…”
Section: Discussionsupporting
confidence: 86%
“…We recently showed estrogen stimulation induced a strong recruitment of a canonical PRC1 (cPRC1) complex containing CBX4 and PCGF2 only after prolonged (24 h) estrogen administration. Because residency of PRC1 complexes is highly dynamic and only a small fraction (∼20%) of complexes are stably interacting with chromatin ( 21 ), we performed CBX4 ChIP assays from double crosslinked chromatin. We reasoned that double crosslinking would increase the likelihood of capturing CBX4 binding at RING1B/ERα co-sites upon 45 min of E2 administration.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study tracking PRC1 occupancy on the chromatin revealed that the majority of RING1B and PRC1 are not stably bound ( 21 ). This result suggests a high degree of turnover in condensate components that is consistent with the observation that proteins within phase-separated condensates can diffuse in and out with ease ( 39 ), such as those at ERα target enhancers.…”
Section: Discussionmentioning
confidence: 99%
“…The PR-DUB subunits BAP1, FOXK2, and ASXL2 were more abundant in the nucleosol (Figure 2F). In contrast, SUZ12 and RING1B were more enriched on chromatin despite their well-established dynamic roles in modifying histones throughout the genome (Alabert et al, 2015;Ferrari et al, 2014 Højfeldt et al, 2019;Huseyin and Klose, 2020;Lee et al, 2015;Youmans et al, 2018). Separation of nucleosol versus chromatin fractions with glycerol gradients revealed that BAP1 sediments in identical high-molecular-weight fractions, suggesting that the complex composition remains unaltered (Figure S2H).…”
Section: Articlementioning
confidence: 99%